MergeToCure: a New Strategy to Allocate Cure in an Epidemic over a Grid-like network Using a Scale-Free Abstraction ⁎. Issue 23 (2018) - Martin, N.; Frasca, P.; Canudas-De-Wit, C.
Abstract: In the context of epidemic spreading over a network the problem of curing some nodes to curb the spreading under budget constraint is often discussed. While strategies exist for heterogeneous networks as scale-free networks (networks with a power-law degree distribution), there is no established link between the scale-free coefficient and the efficiency of the method. Thus, we first present a theoretical result linking the scale-free coefficient and the efficiency of the strategy of allocation in scale-free networks. Then, based on this we derive a new strategy for homogeneous networks as grid-like networks. To do so we use a scale-free abstraction of the network allowing to identify the most interesting zones to cure. Finally, we show that the link between scale-free coefficient and efficiency can also be observed within this version.